Is it possible to find the antinomy between freedom and determinism in political science and ideology? - Jokubaitis, Alvydas (Politologija, 2024)
The aim of the article is the attempt to prove that in empirical political science and political ideologies there is no Kantian antinomy of determinism and freedom. The analysis is based on Kant’s conception of transcendental ideas. His understanding of ideas shows why political science cannot be called empirical. Politics is unimaginable without reasons ability to transcend the world of sense and to think in terms of principles that are independent of it. Political judgements correspond to the requirements of reflexive judgement and not to those of determining judgement. Because of the reflexive nature of political judgement, antinomy is solved to the benefit of freedom. Free choice is the basis of science and ideology.